Some Aspects of the Reliability of Information on the Web - Narayanan, Kulathuramaiyer; Maurer, Hermann; Rizwan, Mehmood (Journal of Universal Computer Science, 2014)
When we look up information in the WWW we hope to find information that is correct, fitting in quantity for our purposes and written at a level that we can understand. Unfortunately, very often one of the above criteria will not be met. A young person looking for information on some aspect of physics may well be frustrated when finding a complex formula whose understanding requires higher mathematics. In other cases, information may be much too voluminous or too short. This seems to indicate that what we need is presentation of material at various levels of detail and complexity. But most important of all, and this is what we are going to discuss in this paper is: how do we know that what we read is actually true? We will analyse this problem in the introductory section. We will show that it is impossible to expect "too much". We will argue that some improvements can be made, particularly if the domain is restricted. We will then examine certain types of geographical information. Detailed research shows that some quantitative measurements like the area of a country or the highest mountains of a country, even if different sources disagree, can be verified by explaining why the discrepancies occur and by trusting numbers if they are identical in very different databases.